Fingering Instabilities in Dewetting Nanofluids - Pauliac-Vaujour, E; Stannard, A; Martin, CP; Blunt, MO; Notingher, I; Moriarty, P; Vancea, I; Thiele, U (American Physical Society, 2008)
The growth of fingering patterns in dewetting nanofluids (colloidal solutions of thiol-passivated gold nanoparticles) has been followed in real time using contrast-enhanced video microscopy. The fingering instability on which we focus here arises from evaporatively-driven nucleation and growth a nanoscopically thin "precursor" solvent film behind the macroscopic contact line. We find that well-developed isotropic fingering structures only form for a narrow range of experimental parameters. Numerical simulations, based on a modification of the Monte Carlo approach introduced by Rabani et al. [Nature 426, 271 (2003)], reproduce the patterns we observe experimentally.